Metodología en la selección de talentos deportivos en el atletismo desde la dimensión social /Methodology in the selection of sports tales in athletics from the social dimension. - Carlos Mojena-Aldana; Elsa Sivila-Jiménez; Michel Alberto Pérez-García (Universidad de Camagüey Ignacio Agramonte Loynaz, 2019)
The selection of talents is today one of the most important aspects in the field of sports and is also one of the reasons why there are numerous theories where the role of those who participate as objects and subjects of said selection is analyzed. It is a systematic and complex process that consists of different stages, in which its initial phase highlights the recruitment, or initial selection, as reflected in the current research, which is necessary to obtain a final result or success in a certain period of time. Ballesteros (1991) and Ozolin (1990), incorporate in their characterization relative aspects with the training and the individual characteristics by tests in the athletics, questions that deepen in the previous references, reason why it justifies, that in matter of selection in this sport, requires the incorporation of indicators that evaluate the development of the subjects, in their natural context, in full interaction with the social environment and factors that shape it. The social dimension is identified in the current study, based on the interaction of endogenous, exogenous and anthropological indicators, during the continuous improvement of the initial selection of talents in school athletics.